2009
DOI: 10.2967/jnumed.109.062554
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Peripheral Benzodiazepine Receptor in the Human Brain Using PET with 11C-AC-5216

Abstract: Peripheral benzodiazepine receptor (PBR) is upregulated in activated glial cells and is therefore a useful biomarker for inflammation in the brain and neurodegenerative disorders. We developed a new PET radioligand, 11 C-AC-N-benzyl-N-ethyl-2-(7-methyl-8-oxo-2-pheyl-7,8-dihydro-9H-purin-9-yl)acetamide ( 11 C-AC-5216), that allows the imaging and quantification of PBRs in monkey and mouse brains. The aim of this study was to evaluate a quantification method of 11 C-AC-5216 binding in the human brain. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…5). PET images showed that the distribution patterns of both 18 F-ligands were consistent with that of 11 C-AC-5216 in the monkey brain and were also similar to those of 11 C-AC-5216 in the human brain, reported previously (26). This result, in addition to the structural similarity of the 3 radioligands, confirmed that the uptake of both 18 F-ligands reflected the distribution of TSPO in the monkey brain.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…5). PET images showed that the distribution patterns of both 18 F-ligands were consistent with that of 11 C-AC-5216 in the monkey brain and were also similar to those of 11 C-AC-5216 in the human brain, reported previously (26). This result, in addition to the structural similarity of the 3 radioligands, confirmed that the uptake of both 18 F-ligands reflected the distribution of TSPO in the monkey brain.…”
Section: Discussionsupporting
confidence: 85%
“…Although several dozen PET ligands have been developed for in vivo TSPO imaging (10,11), radioligands such as 11 C-AC-5216, 11 C-DAA1106, and 18 F-FEDAA1106 had little dissociation in the primate brain (23)(24)(25)(26). The slow kinetics of these PET ligands is a significant disadvantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the kinetics of [ 11 C]AC-5216 has been characterized in normal human subjects (Miyoshi et al, 2009), a side-by-side comparison would be enabled between courses of neuroinflammatory insults in humans and experimental models, toward the establishment of immunotherapeutic interventions in the disease pathogenesis and creation of better genetically engineered animals recapitulating the amyloidosis-gliosis intercontinuum in human diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[159,160] families. Three of these ligands have so far been applied to human subjects [161][162][163], and a comparative PET analysis of nondemented elderly and AD cases was conducted with [ 11 C]DAA1106 [164]. The [24,158].…”
Section: Accepted Manuscriptmentioning
confidence: 99%